2013
DOI: 10.1007/s12603-012-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease and gait and balance impairment in mild to moderate Alzheimer's disease

Abstract: In our sample, AD with cerebrovascular disease had worse gait and balance than AD without cerebrovascular disease. If confirmed, these results may have clinical implications, since cerebrovascular disease can be potentially prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…38 However, this may be due to risk factors such as hypertension, stroke, and arthritis. 4,37 Although in our study, we didn't find a relationship between gait disturbance and comorbid diseases, this relationship has been valued by Inzitari et al 39 We found worst scores on the disability scale RDRS in patients presenting gait disturbance. Patients with greater disability in the early stages of the disease reach gait disturbance sooner, so it could be a good predictor of gait disturbance.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…38 However, this may be due to risk factors such as hypertension, stroke, and arthritis. 4,37 Although in our study, we didn't find a relationship between gait disturbance and comorbid diseases, this relationship has been valued by Inzitari et al 39 We found worst scores on the disability scale RDRS in patients presenting gait disturbance. Patients with greater disability in the early stages of the disease reach gait disturbance sooner, so it could be a good predictor of gait disturbance.…”
Section: Discussioncontrasting
confidence: 48%
“…38 However, this may be due to risk factors such as hypertension, stroke, and arthritis. 4,37 Although in our study, we didn’t find a relationship between gait disturbance and comorbid diseases, this relationship has been valued by Inzitari et al 39…”
Section: Discussionmentioning
confidence: 52%
“…This progressive decline of gait parameters paralleling the evolution of dementia confirms the findings of previous studies . Different factors have been suggested to explain this parallel decline between cognition and gait: the progressive decline of the frontal lobe functions , the involvement of the basal ganglia or the accumulation of vascular lesions . The progressive gait degradation with the course of dementia has been associated with poor clinical outcomes such as falls , institutionalization and mortality .…”
Section: Discussionmentioning
confidence: 99%
“…AD is characterized by loss of neurons and dendritic spins with degeneration of neurofibrils, mainly in the hippocampus and cerebellum ( Mavroudis et al, 2010 ) Cerebellum modulates coordination of movement, and cerebellar dysfunction lacks coordination of voluntary movement and then causes gait disturbance ( Taroni and DiDonato, 2004 ). Several studies suggested that AD induces motor impairments, including dysfunction of gait and balance ( Inzitari et al, 2013 ; Kuwabara et al, 2014 ). In the present study, Aβ 25–35 -induced AD rats showed disturbance of coordination and balance in the rota-rod test.…”
Section: Discussionmentioning
confidence: 99%